2023
DOI: 10.3390/ijms24032448
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Shigella Pathogenesis; Recent Advances

Abstract: Shigella species are the main cause of bacillary diarrhoea or shigellosis in humans. These organisms are the inhabitants of the human intestinal tract; however, they are one of the main concerns in public health in both developed and developing countries. In this study, we reviewed and summarised the previous studies and recent advances in molecular mechanisms of pathogenesis of Shigella Dysenteriae and non-Dysenteriae species. Regarding the molecular mechanisms of pathogenesis and the presence of virulence fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 105 publications
0
12
0
Order By: Relevance
“…S. enteritidis is among the most frequently encountered species, and is mainly found in chicken eggs [ 335 ]. Shigella dysenteriae is a common causative agent of diarrhea, hemorrhagic colitis, and hemolytic uremic syndrome [ 336 ], with a wide arsenal of virulence factors at its disposal [ 336 , 337 ]. Antibiotic resistance is a concern in this case as well [ 338 ].…”
Section: Discussionmentioning
confidence: 99%
“…S. enteritidis is among the most frequently encountered species, and is mainly found in chicken eggs [ 335 ]. Shigella dysenteriae is a common causative agent of diarrhea, hemorrhagic colitis, and hemolytic uremic syndrome [ 336 ], with a wide arsenal of virulence factors at its disposal [ 336 , 337 ]. Antibiotic resistance is a concern in this case as well [ 338 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated a substantial increase in resistance of Prevotella to several antibiotics (clindamycin, penicillin, cephalosporin, tetracycline, amoxicillin, and metronidazole), attributed to the presence of antimicrobial resistance genes or efflux pumps ( Sharma et al., 2022 ). The Shigella bacteria reside in the gastrointestinal tract and are the primary causative agents of bacillary diarrhea or shigellosis in humans ( Pakbin et al., 2023 ). The involvement of increased Shigella and decreased lysozyme in the pathogenesis of intestinal barrier dysfunction during acute necrotizing pancreatitis is evident ( Chen et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…dysenteriae causes illness by invading and damaging the epithelial cells that line the colon, ileum, and rectum in the gastrointestinal tract. This invasion disrupts the normal functioning of these cells, leading to symptoms such as diarrhoea, abdominal cramps, and fever [ 5 ].…”
Section: Introductionmentioning
confidence: 99%